What does the expression l∙w represent

Answers

Answer 1
Answer: It represents Length times width

Related Questions

Suppose the circumference of a circle is 3 pi. What is the diameter?
How is statement B related to statement A? Statement A: If two angles are not vertical, then the angles are not congruent. Statement B: If two angles are vertical, then the angles are congruent. A) Inverse B) Converse C) Conditional D) Contrapositive
Which expression is equivalent to the area of metal sheet required to make this square-shaped traffic sign?A square shaped traffic sign is shown with length of one side labeled as 8x minus 2.
(2+2)^5 + (8+3)^5 Divided by 10?
How do you find the scale factor in 7th grade

Emma earns $6 each time she mows the lawn and $8 per hour for babysitting. She is saving up to buy a new pair of jeans that cost $48. If she mows the lawn x times and babysits for y hours, which graph shows the amount of work she needs to complete to earn at least enough to purchase the new jeans?

Answers

To graph this we find the x- and y-intercepts. The x-intercept would be at 8 and the y-intercept would be at 6.

Explanation:
The equation is 6x+8y=48. An x-intercept is the point where the data crosses the x-axis. All points on this line will have a y-coordinate of 0, so we replace y with 0 and solve:
6x+8(0)=48
6x=48.

Divide both sides by 6:
6x/6=48/6
x=8.
We go to 8 on the x-axis and plot the point.

A y-intercept is the point where the data crosses the y-axis. All points on this line will have an x-coordinate of 9, so we replace x with 0 and solve: 6(0)+8y=48
0+8y=48
8y=48.

Divide both sides by 8:
8y/8 = 48/8
y=6.

We go up to 6 on the y-axis and plot the point. We then draw a line through these two points.

Answer:

Refer the figure.

Step-by-step explanation:

Let x be the number of times Emma mows the lawn

and y be the number of hours Emma babysits

Emma earns $6 each time she mows the lawn and $8 per hour for babysitting i.e. 6x+8y

She is saving up to buy a new pair of jeans that cost $48.

i.e. 6x+8y\geq 48

The y-intercept of the line is the point when x=0,

6(0)+8y=48

y=(48)/(8)

y=6

y-intercept is at (0,6)

The x-intercept of the line is the point when y=0,

6x+8(0)=48

x=(48)/(6)

y=8

x-intercept is at (8,0).

The shaded area is determined by putting x and y zero.

6(0)+8(0)\geq 48

0\geq 48

False so the region is away from origin.

The solution is the shade area above the solid line.

Refer the attached figure.

What are the roots of the equation x2 + 4x - 16 = 0?

Answers

see attached picture for answer

two angles are supplementary the first angle measures 40 degrees what is the measurement of the second angle

Answers

Supplementary angles add up to 180
40+x=180
x=140
The answer would be 160

The numbers 1 through 50 are written with red marker on slips of paper while the numbers 51 through 100 are written with blue marker on slips of paper. All the papers are put into a bag and shuffled. One card is randomly selected. a. Find the probability of selecting a number less than 81 or a number written in red.

Answers

less than 81 is from 80 to 1
that is 80 numbers
80/100=8/10=80%
80%
or a number writtten in red
50/100 are red
50% are red
it says or so it cannot be both
80%-50%=30%

answer is 30%

Find the arc length of AB. Round answer to nearest tenth.

Answers

Answer:

9.8 inches

Step-by-step explanation:

The formula for arc length is (θ/360)2πr

This is where θ represents the measure of the central angle in degrees,

and r represents the radius of the circle.

This said, we can plug our values in.

(80/360)2π7

Simplify.

(2/9)14/π

28/9π

9.7738438112

Round to nearest tenth.

9.8

Answer:

9.8 inches

Step-by-step explanation:

Set up a proportion:

central angle / 360  = arc length / circumference

(80)/(360) = (x)/(14\pi )

360 divided by 14pi is about 8.2, so divide 80 by 8.2 to find x.

x = 9.8 in

A, B, and C are polynomials, where A = n, B = 2n + 6, and C = n2 – 1. What is AB – C in simplest form?A=–n2 + 3n + 5
B=n2 + 6n + 1
C=2n2 + 6n – 1
D=3n2 + 5

Answers

Answer:

AB-C=n^(2) +6n +1

Step-by-step explanation:

Given :

A = n

B=2n+6

C=n^(2) -1

To Find: AB-C

Solution:

Since A=n

B=2n+6

So,AB=2n^(2) +6n

Now since C=n^(2) -1

Thus AB-C=2n^(2) +6n-(n^(2) -1)

AB-C=2n^(2) +6n-n^(2) +1

AB-C=n^(2) +6n +1

Thus option B is correct .

If you would like to find AB - C in simplest form, you can do this using the following steps:

A = n
B = 2n + 6
C = n^2 - 1

AB - C = n * (2n + 6) - (n^2 - 1) = 2n^2 + 6n - n^2 + 1 = n^2 + 6n + 1

The correct result would be B=n2 + 6n + 1.